AQUATIC RECOVERY PROCEDURES FOR NEUROMUSCULAR RE-EDUCATION OF LOWER EXTREMITIES USING THE BAD RAGAZ METHOD (University Arena, 2025)
The Bad Ragaz method is a method of stabilizing and consolidating exercises; is used to treat strengths or locomotor deficiencies, aided by the technique of devices like floating rings for neck, pelvis and ankles. Patient maneuvering by the therapist and hand-held resistance with passive, active and resistive active movements each model can be modified and adapted to a wide variety of orthopedic or neurological diagnoses.Through this paper, we aimed to underline the importance of the Bad-Ragaz therapeutic-aquatic programs for lower limb recovery, given their effectiveness in reeducating associated physical disabilities. Stabilization and consolidation-oriented method, the Bad Ragaz method is used to treat resistance or locomotor deficiencies, aided by the technique of floating rings, neck, pelvis and ankles. Taking into account the results obtained, we consider that hydrokinetotherapy can be recommended as an effective alternative for recovery of deficiencies associated with inferior limbs.
Keywords: aquatic therapy; spinal cord injuries; swimming